Total phenolics, flavonoids, antioxidant activity, and α-glucosidase inhibitory activity of ornamental pepper and several other lines - Sahid, Zulfikar Damaralam; Syukur, Muhamad; Maharijaya, Awang; Nurcholis, Waras (Ornamental Horticulture, 2022)
Ornamental chili is a type of chili plant that favors the value of beauty but still has a spicy taste. It generally has a purple fruit color because they contain anthocyanins. The biochemical content in ornamental chili is believed to have benefits for human health. This study aims to identify several biochemical compounds in several genotypes of ornamental chili and pure lines. The study was conducted using the microplate method which was repeated three times. The research design used was a completely randomized design with a single factor genotype. Sixteen genotypes of chili were used, consisting of 4 genotypes of ornamental chilies and 12 genotypes of pure lines. The results showed that the ornamental chili genotype Nazla IPB contained 83.27% α-glucosidase inhibitory activities. The pure lines genotype F10 145174-9-7-1-5-3-1-2-5 contained the second-largest α-glucosidase inhibitory activities (80.67%) and the highest antioxidant DPPH (15.40 μmol TE g.-1 extract). The highest antioxidant of the FRAP method was shown in Adelina IPB’s ornamental chili. The correlation between biochemical parameters showed that DPPH-AGI was significantly positively correlated and FRAP-AGI was negatively correlated. It is concluded that the information in this study can be the basis for the development of functional ornamental plants in future ornamental chili breeding research.